Anda di halaman 1dari 2

Resolver: 3x 1 2x 1

15. x
1. 7x 7 = 1 x 7 3
2. 5x 7 = 101x 103 16. (x + 2)2 = x2 + 2x + 6
3. 3x 1 = x + 2 + x
17. (x + 3)2 = (x - 2)2 5
1 9
4. 5x - =x+
2 2 18. (x + 4)2 + 6 = x2 + 2x
3x 17 x 21
5.
5
+
5
=
5
+
3
19. (x + 1)2 (x - 1)2 + 12 = 0
6. 4x (2x - 1) + x = 2x (2 + x) x 20. (x + 1)2 + (x - 2)2 = (x + 2)2 + (x - 1)2
7. x + (x + 3)(x 3) = 3 + x(x + 1) 21. (x + 3)(x - 3) 2(x + 1) = x(x - 1) 3
8. 7x [(x + 5) (3x 1)] = 12 22. (x + 2)(x + 3) = x2 + 4x + 10
3x 5
9. - =x1 23. x2 + 7x 3 = (x + 5)(x + 4)
2 3
24. (x + 7)(x + 3) = (x + 8)(x + 1)
x 1 x
10. 2
3 4 25. (x + 8)(x 8) = x2 4x

11.
x2 x4
2 26. (x + 1)(x2 x + 1) (x - 1)(x2 + x + 1) =
4 2 2(x - 2)
x3 x1
12.
5

3
2 27. (x - 2)(x2 + 2x + 4) = x3 4
2 3
3x 2x x 28. (x + 3)(x 3x + 9) = 2x
13. 2
4 3 2 2
29. (x + 5x + 25)(x - 5) 5 = 86
x 4
14.
x 1 5
30. (x2 + 7x + 49)(x - 7) = -218

Resolver: x 1 7(x 1) x 2 x 2
15.
1. 3x 2 = x + 8 3 24 8 8
2. x + 2x + 3x = 1 + 2 + 3 16. (x + 2)2 = 32 + (x - 2)2
3. 3x 1 = 4x + 4 2 2
1 7
17. (x + 3) = (x + 2) + 17
4. x 2x 2 2 2
3 3 18. (x + 2) x = 2x (x - 2)
1
5. 2x 1 x 1 19. (x + 6)2 + 12 = x2 + 3x + 1
7 2 2
6. 4x + 2 x = x 3 + 2x 20. (x - 5) + 4 = x 7x
7. 5x + (2x + 3) = 7x (5 - x) 21. (x + 4)(x + 5) = (x + 2)(x + 6)
8. 7x [(x + 4) (2x + 1)] = 10 22. (x + 6)(x + 1) = (x + 2)(x + 3)
2x 3 x 1 23. (x + 5)(x 5) x2 = -2x + 25
9.
2 5 2
24. (x + 5)(x - 3) = x + x + 1
3x 1 2x 1
10. x 25. (x - 4)(x - 3) = x2 + 2x + 8
7 3
2
3x 1 4 x 1 x 26. (x + 3)(x 3x + 9) = 91
11. 0
4 3 6 27. (x - 4)(x2 + 4x + 16) = 936
x 1 x 1 2 3
12. 28. (x + 8)(x + 8x + 64) x = 2x
3 6 4 2
1 2x x4 29. (x - 2)(x2 + 2x + 4) x3 = 8x
13. 1
9 6 30. (x + 5)(x2 5x + 25) (x - 3)(x2 + 3x + 9) =
x2 x3 x4 x5 49x
14.
2 3 4 5